Application of Organomineral Fertilizers to Winter Wheat in the Rostov Region - Yermilov, Artyom; Kamenev, Roman; Turchin , Vladimir; Kameneva, Vera (KnE Life Sciences, 2021)
Modern crop cultivation technologies are based on various methods of seed and plant treatment using environmentally friendly drugs that stimulate growth and the development of the plants, and increase their productivity and stress resistance. It has been established that the use of organic fertilizers positively affects the vital signs, yield and grain quality of cereal plants. When cultivating winter wheat on the southern chernozem of the Kamensky district (in the Rostov region), the organic fertilizers Router (0.5 or 0.25 l / ton) and Leyli (0.25 l / ton) were used for seed treatment, and Soft Guard (0.2 l / ha) and Humiful Pro (0.2 l / ha) were used in spring tillering and in the flag leaf phase against the background of mineral nitrogen fertilizers in a dose of N32P32K32; the frozen-thawed soil was fertilized with ammonium nitrate in a dose of N40 and foliar fertilization was conducted with carbamide in the heading phase using a dose of N20. This increased the average grain yield by 64.2-64.8% compared with the control variant and by 31.4-32.4% compared with the use of mineral fertilizers. The maximum yield gain was achieved by using the soft-root organic fertilizers Soft Guard (0.2 l / ha) and Gumiful Pro (0.2 l / ha) against the background of mineral fertilizers and seed treatments with Router (0.5 l / ton). Keywords: winter wheat, southern chernozem, organic fertilizers